Using technology for improving attitudes of students with intellectual disability towards mathematics - Baglama, Basak (2019)
Advancements and innovations in technology enhanced learning various skills of individuals with intellectual disability. These skills primarily include reading, writing and mathematical skills and attitudes of students on learning these skills are really important. Therefore, it is important to reveal whether technology really helps students with intellectual disability to improve their attitudes towards learning mathematics through technology. This study aims to determine the effectiveness of using technology to improve attitudes of students with intellectual disability towards mathematics. Pre-test and post-test single group design as an experimental research method was used in the study. A total number of 6 students with intellectual disability participated in the study. Students were subjected to teaching sessions of mathematical problem solving presented with computer aided videos consituted with direct instruction. Data were collected before and after teaching sessions in order to reveal the differences between pre and post teaching sessions through a survey. Results showed that students’ attitudes towards mathematics improved after teaching sessions presented with computer aided videos. Results are discussed with relevant literature and recommendations for future research and practices are provided.